Model-Model Pembangkitan Data Sintetis Untuk Curah Hujan Harian Di Wilayah Brantas Tengah - Soetopo, Widandi; Limantara, Lily Montarcih; Sayekti, Rini Wahyu; Purwati, Endang; Chandrasasi, Dian; Ilham, Muhammad; Rahmadi, Agung (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2015)
This research is for finding the suitable synthetic daily rainfall generating model in the Middle Brantas River Basin - East Java. There are 7 models being considered, 4 single-site models, (1) the two-part, (2) the transition probability matrix, (3) the resampling, and (4) the time series, and 3 multisite models, (5) the conditional, (6) the extension of single site Markov chain, and (7) the random cascade. All time-series produced by the models are then tested statistically. The results show that the differences between the historial time series and the synthetical time series are not too significant. It turn out that the synthetic time series of multisite models are better than the synthetic time series of single-site models.Keywords: generating model, synthetic data, daily rainfall.